Post 90-day outcomes of acute ischemic stroke patients following thrombectomy: analysis of real-world data - Qureshi, Adnan I.; Baskett, William I.; Bhatti, Ibrahim A.; Ovbiagele, Bruce; Siddiq, Farhan; Ford, Daniel E.; Gomez, Camilo R.; Hanley, Daniel F.; Shyu, Chi-Ren (Frontiers in Neurology, 2025)
BackgroundPrevious studies have focused on 90-day outcomes in acute ischemic stroke patients who undergo thrombectomy, although long-term outcomes are not well understood. We compared the long-term rates of survival and new stroke recurrence among acute ischemic stroke patients who did and did not undergo thrombectomy.MethodsUsing the Oracle Real-World Data (a de-identified large data source of multicenter electronic health records covering the period of January 2016 to January 2023), we analyzed 3,934 acute ischemic stroke patients who underwent thrombectomy and 3,934 propensity-matched controls of acute ischemic stroke patients who did not undergo thrombectomy. The risk of death or palliative care and new stroke following >90 days post-admission was ascertained using Cox proportional hazards regression analysis to adjust for potential confounders. We also estimated the rate of new stroke and palliative care-free survival using Kaplan–Meier survival analysis.ResultsAmong 3,934 acute ischemic stroke patients who underwent thrombectomy, 2,660 patients either died or received palliative care or developed new stroke (median follow-up period of 775 days post-initial stroke admission; interquartile range Q1 = 356 days, Q3 = 1,341 days). The 2-year new stroke and palliative care-free survival were 36.6 and 45.8% among patients who did and did not undergo thrombectomy, respectively (adjusted hazard ratio [HR], 1.19, 95% confidence interval [CI], 1.12–1.26). The risk of palliative care or death was not different (adjusted HR, 0.89, 95% CI, 0.77–1.02) between both groups, but the risk of new stroke was higher among patients who underwent thrombectomy (adjusted HR, 1.25, 95% CI, 1.18–1.33).ConclusionAcute ischemic stroke patients who undergo thrombectomy are at greater risk of new stroke, palliative care, or death after 90 days, primarily driven by the occurrence of stroke. There is a need for closer surveillance and enhanced recurrent stroke prevention in this high-risk group.